Analisis Karakter Kepemimpinan Organisasi Badan Eksekutif Mahasiswa Keluarga Mahasiswa Institut Pertanian Bogor - Alya Putri Azhari; Ardina Latifah Azzahra (PUBLICNESS: Journal of Public Administration studies, 2022)
This Leadership is the main point in an organization that affects the running of the organization, the success of work programs, member performance, member resilience which is largely determined by the leader. A leader has a leadership style that affects its performance and that of its members. Organizations become a meeting place for two or more people who have the same goals with a certain structure that binds them.  The purpose of this study was to analyze the effect of student organization leadership style on the success of the work program. This study used a cross sectional study method because the data were collected at one time and were not continuous and used a survey method. BEM KM IPB 2020/2021 The Zilenial Cabinet as a forum for developing IPB University students, has a leadership pattern that is different from the leadership pattern of previous years. The leadership pattern of BEM KM IPB tends to support its students to be creative and innovate as much as possible. The results of this study are that there are characteristics that are reflected, namely fairness, high curiousity, being able to motivate, and self awareness. Justice is reflected in the process of division of work tasks. Curiousity seen from the leader’s willingness to accept staff opinions and input. The character that is able to motivate is reflected in the leader who encourages staff to perform. And the character of self-awareness is analyzed through an open leader and willing to accept criticism.